Overexpression of Long Non-coding RNA 4933425B07Rik Causes Urinary Malformations in Mice - Tan, Lihong; Yu, Minghui; Li, Yaxin; Xue, Shanshan; Chen, Jing; Zhai, Yihui; Fang, Xiaoyan; Liu, Jialu; Liu, Jiaojiao; Wu, Xiaohui; Xu, Hong; Shen, Qian (Frontiers in Cell and Developmental Biology, 2021)
Congenital anomalies of the kidney and urinary tract (CAKUT) is a common birth defect and is the leading cause of end-stage renal disease in children. The etiology of CAKUT is complex and includes mainly genetic and environmental factors. However, these factors cannot fully explain the etiological mechanism of CAKUT. Recently, participation of long noncoding RNAs (lncRNAs) in the development of the circulatory and nervous systems was demonstrated; however, the role of lncRNAs in the development of the kidney and urinary tract system is unclear. In this study, we used the piggyBac (PB) transposon-based mutagenesis to construct a mouse with lncRNA 4933425B07Rik (Rik) PB insertion (RikPB/PB) and detected overexpression of Rik and a variety of developmental abnormalities in the urinary system after PB insertion, mainly including renal hypo/dysplasia. The number of ureteric bud branches in the RikPB/PB embryonic kidney was significantly decreased in embryonic kidney culture. Only bone morphogenetic protein 4 (Bmp4), a key molecule regulating ureteric bud branching, is significantly downregulated in RikPB/PB embryonic kidney, while the expression levels of other molecules involved in the regulation of UB branching were not significantly different according to the RNA-sequencing (RNA-seq) data, and the results were verified by quantitative real-time polymerase chain reaction (RT-PCR) and immunofluorescence assays. Besides, the expression of pSmad1/5/8, a downstream molecule of BMP4 signaling, decreased by immunofluorescence. These findings suggest that abnormal expression of Rik may cause a reduction in the ureteric bud branches by reducing the expression levels of the ureteric bud branching-related molecule Bmp4, thus leading to the development of CAKUT.